Mean Platelet Volume as Potential Predictor of Intradialytic Hypertension - Soelistyoningsih, Dwi; Wira, Daramatasia; Qodir, Abdul; Rifa'i, Achmad (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Abnormalities in platelets can lead to severe consequences renal and systemic blood flow. The aim of this study is to determine the predictive ability of platelet indices (mean platelet volume, platelet-lymphocyte ratio, and platelet count) in relation to changes in blood pressure before and immediately after hemodialysis. This study included 98 patients undergoing hemodialysis at the RSU UMM Malang, aged ≥18 years, hemodialysis duration > 1 month, and signing informed consent. The predictor variable were MPV, PLR, and platelet count and the outcome was the incidence of IDHT. There was a significant difference in the blood pressure of patients undergoing hemodialysis before compared to immediately after hemodialysis, for both systolic and diastolic blood pressure (p < 0.001). To assess the sensitivity and specificity of the accuracy of the platelet count, MPV, and PLR markers in predicting IDHT, ROC curve was created based on the difference in systolic blood pressure before-after hemodialysis. From the receiver operating characteristic (ROC) curve, it was found that the MPV value was the highest above the diagonal line compared to PLR and platelet count with an MPV cut-off value was 9.15. This indicates that MPV is the best predictive marker compared to the other models.